The Implementation Of Wattpad Application On Improving Student Reading Comprehension Skill At SMAN 6 Bengkulu Tengah - Syerliana, Syerliana; Riswanto, Riswanto; Haryanto , Endang (The Future of Education Journal, 2026)
This study aims to describe the process of implementing the Wattpad application as an English learning medium for reading comprehension among students at SMA Negeri 6 Bengkulu Tengah, to analyze students’ perceptions of the use of Wattpad as a learning medium for reading comprehension, and to identify and analyze English teachers’ perceptions regarding the challenges and opportunities during the implementation of Wattpad in reading comprehension instruction. This study employed a descriptive qualitative approach, with data collected through classroom observations, interviews, and documentation involving one English teacher and eight eleventh-grade students selected through purposive sampling. The results indicate that Wattpad is used as a learning medium that supports reading activities through the selection of reading texts tailored to students’ proficiency levels and interests, followed by discussion activities and reading comprehension tasks. Students showed positive perceptions toward the use of Wattpad because the reading texts were considered more engaging, contextual, and easier to understand compared to those found in textbooks, thereby enhancing students’ engagement and motivation in reading. From the teachers’ perspective, the use of Wattpad provides more opportunities than challenges, particularly in supporting digital literacy and helping students comprehend reading texts in a more natural way through various instructional activities such as identifying main ideas, discussing vocabulary and moral values, and creating summaries. Nevertheless, several challenges were identified during the implementation, including limited internet access, differences in students’ language proficiency levels, and the need for careful selection of reading materials. Overall, with appropriate teacher guidance and suitable selection of reading materials, the Wattpad application can be used as a relevant learning medium to support English reading comprehension skills at the secondary school level.